Increasing Integrative Negotiation in European Organizations Through Trustworthiness and Trust - Elgoibar, Patricia; Medina, Francisco J.; Euwema, Martin Claes; Munduate, Lourdes (Frontiers in Psychology, 2021)
Integrative negotiation in which employers and employees create value is a major necessity in the current challenging context. Collective labor negotiations in organizations are traditionally focused on mostly distributive issues, such as pay, working hours and holidays. However, the current situation demands the inclusion of other issues of a potentially more integrative nature, such as telework, sustainability and risk prevention, the enhancement of which is a major challenge for organizations. In this study, we explore the negotiation process between management and employee representatives (ERs), analyzing the roles of trust and trustworthiness. We collected data from 614 human resources managers from different organizations in eleven European countries. The results confirm that ERs who management perceive to be trustworthy have a greater influence on negotiation, particularly with regard to integrative as opposed to distributive issues, and that trust partially mediates this relationship.